AN ANALYSIS OF THE RELATIONSHIP BETWEEN EXCHANGE RATE FLUCTUATIONS AND UGANDA’S TRADE BALANCE (2000-2020) - Bukenya Jonathan (Uganda Christian University, 2024)
This dissertation investigates the relationship between exchange rate fluctuations and Uganda’s trade balance with a focus on how this fluctuation in the Ugandan shilling affect the country’s export and import dynamics. Uganda’ s trade balance has persistently been in a deficit primarily due to its dependence on imports like oil and industrial inputs while exports mainly being agricultural products. The study aims to assess the impact of exchange rate movements on these trade components and offers insights into the implications for Uganda’s overall economic stability. This paper employs a mixed methods approach of both qualitative and quantitative data to analyze the effects of exchange rate fluctuations on trade. Secondary data sources include reports from Bank of Uganda (BOU), world bank and other financial institutions. The methodology involved testing for multicollinearity, autocorrelation and conducting a correlation analysis to establish the relationship between exchange rates and trade balance indicators. The ordinary least squares (OLS) regression model was used to assess relationship between exchange rate fluctuations on exports and imports. Exchange rate depreciation can make Ugandan exports more competitive on the international market potentially improving the trade balance. However, the fluctuation associated with this volatility creates uncertainty which can deter investment in export sectors resulting in less stable export growth. Additionally, depreciation raises cost of essential imports, worsening the trade deficit. The incomplete pass through of exchange rate changes into domestic prices further complicates the impact, making trade outcomes unpredictable. The study concludes that while exchange rate fluctuations can offer short term benefits to exports, its overall impact on Uganda’s trade balance is negative due to the increased cost of imports and uncertainty it introduces into the economy. To mitigate these effects, the dissertation recommends a multifaceted approach including the accumulation of foreign exchange reserves, promotion of export diversification, strengthening regional economic integration and continuously monitoring exchange rate movements to adjust policies proactively are also suggested as vital steps towards achieving a more stable trade environment.